(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, the development of strategic management skills in the activities of educational specialists in general education schools, certain criteria of its uniqueness in the theory of educational management, the unique characteristics of the strategic management education system, the Information is provided on the effects of the management of the development of the educational system on the introduction of technological, pedagogical, organizational innovations, and the means of changing the relations of the educational institution with partners and competitors.